Development of indigenous biofilm for enhanced biogas production from palm oil mill effluent - Abdul Hamid, Nurfarhana; Alam, Md. Zahangir (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Palm oil has its huge market in the industry which means that it also a produces a large amount of palm oil mill effluents (POME) despite it can create environmental issue due to its characteristics. POME has high organic content that can be a great source for production of biogas. Biogas produced from POME can be used as power generation and increased the economic potential. The production of biogas had been widely discovered, however, it had a problem with the low yield of biogas produced. Thus, in order to overcome this problem, a technique is used by using indigenous biofilm as a simultaneous pretreatment and biogas production. The indigenous biofilm formation was acted as the pretreatment for the digestion and later it was used to produce biogas that enhanced the hydrolysis process of anaerobic digestion. POME was used as the substrate that undergoes anaerobic digestion under several controlled parameters. The operating pH, total suspended solid (TSS) and biofilm were found to be 4-8, 1.5- 4.5 % and 2-4 g respectively throughout the experiment. The preliminary experiments found the suitable biofilm producer from POME where the optical density of the microorganism in the range of 1.5-3.043. Therefore, a further experiment was done to find the optimum parameter for biogas production. Based on the experiment conducted, the optimum conditions for the biogas production were at pH 8, TSS of 3.0% and biofilm used of 3 g and the highest biogas yield was 382 ml within 5 days. Thus, it is supposed that anaerobic digestion of POME using indigenous biofilm to produce biogas could be used as a solution to reduce the source of pollution to the environment.